Pneumonia Verminosa pada Kucing Lokal yang Terinfeksi oleh Aelurotsrongylus sp (VERMINOUS PNEUMONIA IN DOMESTIC CAT INFECTED BY AELUROSTRONGYLUS SP) - Winaya, Ida Bagus Oka; Berata, I Ketut; Kardena, I Made; Oka, Ida Bagus Made (Jurnal Veteriner; Vol 13 No 4 (2012), 2013)
The aim of the study was to evaluate the pulmo pathological changes of domestic cat infected byAelurostrongylus sp. A total of 15 cats were examined at Faculty of Veterinery Medicine, Udayana Universityduring 2010. Ten out of 15 cats showed sneezing, whereas the remains showed serous rhinitis and sneezing.Macroscopic and microscopic changes were observed mainly on pulmo samples. Hyperemias on caudalislobes and pleura effusion were found in the pulmo. The pulmo tissue was fixed on 10 % neutral bufferformalin and stained with haematoxilin-eosin (HE) for histopathological examination. Aelurostrongylus spwas present in the alveoli lumen of the lung samples. Meanwhile, the alveoli septa of the lung wereobserved thicker and infiltrated with neutrophils, plasma exudates and erythrocytes. Pleural effusion wasmainly consisted of eosinophilic substances. It is concluded that verminous pneumonia in domestic catinfected with Aelurostrongylus sp was an acute infection.
Keywords: Aelurostrngylus sp, lung, interstitialis pneumonia